Antibacterial activity and biological performance of a novel antibacterial coating containing a halogenated furanone compound loaded poly(L-lactic acid) nanoparticles on microarc-oxidized titanium - Cheng YC (Dove Medical Press, 2015)
Yicheng Cheng,1,2,* Xianghui Zhao,3,* Xianghui Liu,2,* Weige Sun,2 Huifang Ren,1 Bo Gao,1 Jiang Wu1 1State Key Laboratory of Military Stomatology, Department of Prosthodontics, School of Stomatology, Fourth Military Medical University, Xi’an, People’s Republic of China; 2Department of Stomatology, Jingdu Hospital, Nanjing, People’s Republic of China; 3Institute of Neuroscience, School of Basic Medicine, Fourth Military Medical University, Xi’an, People’s Republic of China *These authors contributed equally to this work Abstract: Titanium implants have been widely used for many medical applications, but bacterial infection after implant surgery remains one of the most common and intractable complications. To this end, long-term antibacterial ability of the implant surface is highly desirable to prevent implant-associated infection. In this study, a novel antibacterial coating containing a new antibacterial agent, (Z-)-4-bromo-5-(bromomethylene)-2(5H)-furanone loaded poly(L-lactic acid) nanoparticles, was fabricated on microarc-oxidized titanium for this purpose. The antibacterial coating produced a unique inhibition zone against Staphylococcus aureus throughout a 60-day study period, which is normally long enough to prevent the infection around implants in the early and intermediate stages. The antibacterial rate for adherent S. aureus was about 100% in the first 10 days and constantly remained over 90% in the following 20 days. Fluorescence staining of adherent S. aureus also confirmed the excellent antibacterial ability of the antibacterial coating. Moreover, in vitro experiments showed an enhanced osteoblast adhesion and proliferation on the antibacterial coating, and more notable cell spread was observed at the early stage. It is therefore concluded that the fabricated antibacterial coating, which exhibits relatively long-term antibacterial ability and excellent biological performance, is a potential and promising strategy to prevent implant-associated infection. Keywords: microarc oxidation, osteoblasts